History of Prague towns until the early 15th century - Goliński, Mateusz, 1960- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2024)
The aim of this book is to introduce the reader to the organization of medieval Prague up to the early 15th century with a focus on the first two essential phases of agglomeration development: early urban and post-charted. Prague was a so-called "multi-part town", consisting of several municipalities and separate urban complexes. This publication examines these Prague towns, their inhabitants, and the institutions that served them, as well as many events and places not connected directly to this book's "urban" subject but which nevertheless constitute an inseparable background and significantly influenced the whole community of Prague.